Determinants of M-Payment Use in Muslim Millennial Generations: Moderation Effects of Knowledge about Riba - Alya Laili Utdkhiati (FEBI UIN Sunan Kalijaga, 2022)
The large amount of using smartphones makes businessmen and scientists create an application where it could be used as one of the ways for cashless payments. One of the tools for cashless payments uses a smartphone application called “Mobile Payment” or M-Payment. The development of M-Payment does not lose the concerns of a muslim towards the idea of syariah. The purpose of this research is to explore the factors that influences the users of M-Payment which are the millennial generation muslims in yogyakarta. This research uses 214 sample that are submitted through an online survey. The data will be processed using the Partial Least Square Structural Equation Modeling (PLS-SEM) approach with a SmartPLS 3.0. The results from the data analysis reveals the convenient variable, comparative variable, and risk perception significantly affects the users intention to acquire M-Payment. On the other hand, the beneficial variable, religiosity shows an insignificance affect of the users intention to acquire M-Payment. However, it shows that the effect of modern knowledge about riba does not moderate in this research. Therefore, M-Payment is able to give advantages, convenience, and safety towards the millennial generation of muslims. Besides that, the concerns of muslims towards the idea of syariah does not affect their intention to use M-Payment